Blind equalization based on T/4 fractionally spaced decision feedback equalizer with RLS algorithm - Ying XIAO (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
To further improve the performance of blind equalization based on T/4 fractionally spaced decision feedback equalizer, RLS algorithm is adopted to update the weights of equalizer according to simplified constant modulus algorithm (CMA) cost function. CMA cost function is simplified to meet second norm form in this work, and then the forward filter of equalizer with T/4 fractionally-spaced updates by RLS algorithm and the feedback filter of equalizer with symbol-spaced updates by gradient descent algorithm. Computer simulation results show that the algorithm proposed in this work has faster convergence rate and lower mean square error compare with blind equalization based on symbol-spaced and T/4 fractionally-spaced decision feedback equalizer based on gradient descend algorithm.DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2156